The Manifestation of the Mahdist Beliefs in the Work of Nizami Ganjavi - Mustafayev, Elnur (Scholarya Demo Journal of Ruby, 2021)
This article investigates the issue of Mahdist beliefs (salvation expectation) as manifested in the work of the great Azerbaijani poet Nizami Ganjavi. The Mahdist concept, which has long piqued the interest of Azerbaijani scholars and writers, is one of the most prominent issues in Islam. From this perspective, Azerbaijani theologians and philosophers have extensively developed the topic of belief in Mahdi. In this article, the author delves into several aspects of Mahdist ideas (salvation) in the work of Nizami Ganjavi, a brilliant Azerbaijani poet and thinker regarded as one of the world’s best representatives of literature (1141-1209). Belief in the Mahdi has been one of the most inspiring topics for poets because it is founded on universal values, a just state and society, and a happy and prosperous life. Nizami Ganjavi used the ideas of this concept in his work to call on the judges and society of the time to do good deeds, serve people, and build just states, as well as individual and social evolution.